Architecture and routing protocols for internet of vehicles: a review. (14th June 2022) - Ajaz, Farhana; Naseem, Mohd; Sharma, Sparsh; Dhiman, Gaurav; Shabaz, Mohammad; Vimal, S.
Modern vehicles should be able to commute a tremendous amount of data and information within their neighbourhood. To incorporate the requirements of modern vehicles, the conventional vehicular ad hoc network (VANETs) are emerging to the internet of vehicles (IoV). IoV keeps all the smart vehicles connected with the help of sensors, GPS, entertainment system, brakes and throttles. These devices send and store their data with the help of cloud. This paper intends to contribute to the review of IoV, its challenges, characteristics and application. A detail discussion on architectures and routing protocols along with its classification is also discussed. This paper ought to guide and motivate researchers working in the area of IoV to develop scalable and efficient routing protocols.